Penerapan Moderasi Beragama Dalam Masyarakat Di Madrasah Aliyah Swasta Al-Hikmah Way Halim Bandar Lampung - khoiri, Akhmad; Hendri Jaya; Asep Bambang S.; Nando Apriyansyah; Usman (Al Mufid, 2023)
ABSTRACT Conflict problems that occur in society are due to the low level of mutual respect between groups, so it often ends up being a growing humanitarian disaster. Religious moderation is actually the key to creating tolerance and harmony, both at the local, national, and global levels. The choice of moderation by rejecting extremism and liberalism in religion is the key to achieving balance for the preservation of civilization and the creation of peace. The goal of this study is to provide an understanding of religious moderation in society through education so that the next generation is prepared to enter a multicultural society. The method used in this study is a qualitative method. According to the results of the research conducted, the application of religious moderation in society is needed in the world of education in order to provide moderation provisions to the younger generation and prioritize moderation attitudes in society.